2010
DOI: 10.1093/europace/euq331
|View full text |Cite
|
Sign up to set email alerts
|

Germline and somatic mosaicism for a mutation of the ryanodine receptor type 2 gene: implication for genetic counselling and patient caring

Abstract: We identified a heterozygous p.Arg2401His mutation of RYR2 by sequencing the DNA of a 7-year-old girl who was referred for catecholaminergic polymorphic ventricular tachycardia (CPVT). Using high-resolution melting assay, we have demonstrated a mosaicism for this mutation in her asymptomatic mother which illustrates the benefit of extensive genetic analysis in CPVT, in particular regarding genetic counselling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…Furthermore, even if it is a rare event, germinal and somatic mosaicism may occur in an asymptomatic parent, as reported in 2 studies. 24,28 Somatic mosaicism is not investigated in most of the clinical diagnostic laboratories and requires additional tissues samples to analyze parental urinary cells, hair roots, or buccal epithelium DNA. Germinal mosaicism is only investigated when the same mutation is identified in 2 siblings and not identified in DNA from the parental blood.…”
Section: Ryr2 Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, even if it is a rare event, germinal and somatic mosaicism may occur in an asymptomatic parent, as reported in 2 studies. 24,28 Somatic mosaicism is not investigated in most of the clinical diagnostic laboratories and requires additional tissues samples to analyze parental urinary cells, hair roots, or buccal epithelium DNA. Germinal mosaicism is only investigated when the same mutation is identified in 2 siblings and not identified in DNA from the parental blood.…”
Section: Ryr2 Mutationsmentioning
confidence: 99%
“…Nevertheless, several clinical investigations suggested that a single CASQ2 mutation could represent a potential susceptibility for ventricular arrhythmias in some subjects. 10,28,45 The origin of the variability among subjects of a same family is still unknown. Two nonsynonymous polymorphisms, Thr76Ala and Val76Met, have been described in CASQ2 in both white and Asian populations, but to our knowledge their possible mild functional effect has not been studied.…”
Section: Casq2 Mutationsmentioning
confidence: 99%
“…Importantly Recently, cases of mosaicism in CPVT were described 30,31 and this can lead to tragic consequences, since silent mutation carriers are at risk for arrhythmic events 12 . The manifestations and severity of symptoms of the disease in a carrier of somatic and germline mosaicism depend on several aspects, such as the degree of mosaicism and the gene involved 32 .…”
Section: Pathophysiology Of Arrhythmias Genetic Basismentioning
confidence: 99%
“…Roux-Buisson et al reinforced the fact that the possibility of germline mosaicism in asymptomatic parents justifies systematic genetic screening of sibling of a sporadic proband, even if the standard methods failed to clearly detect the mutation in the parents 31 .…”
Section: Pathophysiology Of Arrhythmias Genetic Basismentioning
confidence: 99%
“…Among patients with exertional syncope, polymorphic VT and normal QTc, nearly 50% have putative RyR2 mutations causing CPVT(13) and nearly 20% of these RyR2 mutations are de novo . (13) Since sporadic cases of CPVT can be due to germ-line mosaicism in one of the parents,(13, 14) systematic genetic screening of the proband’s siblings should be done even if standard methods fail to clearly detect the mutation in the parents. (14) A tiered-approach in screening for RyR2 mutations due to clustering of known CPVT mutations in certain exons can be used to lower the cost.…”
Section: Introductionmentioning
confidence: 99%